Influence of ultrasound on the instantaneous synthesis of tridimensional α-Ni(OH)2 nanostructures and derived NiO nanoparticles. Issue 32 (28th August 2015) - Cabanas-Polo, S.; Gonzalez, Z.; Sanchez-Herencia, A. J.; Ferrari, B.
<x xml:space="preserve">Abstract</x> Nickel hydroxides present an extraordinary importance in the development of electrochemical devices.